Prevalence of Metabolic Syndrome and Factors Associated with it among Women in Felda Palong, Gemas, Negeri Sembilan - Mat Hussin, Azizah (2006)
A cross sectional study was carried out to assess the diet, physical activity and the prevalence of metabolic syndrome (MS) of 106 women aged 45 to 60 years old living in Felda Palong 4, 5 and 6, Gemas, Negeri Sembilan. The data collection processes included interviews, anthropometric measurements, blood pressure measurements and blood lipid sample collection. Out of the total sample, 67.0% were Malays, 29.2% were Indians and 3.8% were Chinese. The educational level of respondents (37.7%) was primary school level. Most of the respondents were housewives (70.8%), with a majority of the respondents (60.4%) earning between RM400 and RM699 per month. For the anthropometric measurements, almost half of the respondents (47.2%) were overweight (Body Mass Index (BMI) 2 25.0 - 29.9). Majority of the respondents (74.5%) had waisthip- ratio (WHR) of more or equal to 0.85 and 81.1% had waist circumferences (WC) equal to or greater than 80 cm. The prevalence of hypercholesterolemia (total cholesterol (TC) 2 6.2mrnol/L) among respondents was 31.1%. Raised Low Density Lipoprotein- Cholesterol (LDL-C) was found in 43.4% of the respondents while low levels of High Density Lipoprotein- Cholesterol (HDL-C) were evident in 14.2% of the respondents. The prevalence of high blood pressure and high blood glucose were 47.2% and 21.7% respectively. The dietary pattern of the respondents showed that their main sources of carbohydrate were rice and white bread. Their main sources of protein were chicken and fish while their sources of vitamins and minerals were fruits and vegetables. A high percentage of respondents were deficient in nutrients like potassium, vitamin C, fiber and calcium that were found to be lower than the Malaysian Recommended Nutrient Intake (RNI) and Daily Reference Value (DRV). On the other hand, the mean intakes of protein, carbohydrates, total fat, sodium, vitamin A, vitamin E and iron were found to be more than RNI and DRV. For physical activity, the mean kcal spent for physical activity was 1843+355. Most of the respondents (55.7%) were in the category of moderate PAL. By using International Diabetes Federation (IDF) criteria, the prevalence of metabolic syndrome significantly increased from 48.1% (NCEP ATPIII) to 54.7% (r = 0.724, ~ ~ 0 . 0 1R)e.s pondents with metabolic syndrome had significantly higher mean BMI, WC, WHR, systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting plasma glucose (FPG), LDL-C and lower mean of HDL-C. BMI, WHR, SBP, DBP, FPG, triglycerides and HDL-C were found to be significantly associated with MS. The mean energy intake was 1846k450 kcal for subjects with MS and 1927f521 for subjects without MS, both lower than the Malaysian RNI (2180 kcal for female). Respondents with MS had higher protein, carbohydrate, total fat and sodium intakes whereas respondents without MS had higher energy intake, cholesterol, vitamin A, vitamin C, potassium, fiber, calcium and iron intakes. However, these differences were not statistically sigruficant except for vitamin C (p<0.05). The results s h d that intake of iron, d u r n and total fat were sigruficantly associated with metabolic syndrome while protein, vitamin A, vitamin C, ca-d fiber intake were not siwcant. In conclusion, this study found that there were associations between anthropometric measurements, blood pressure, fasting plasma glucose and lipid profiles also found that there were associations with metabolic syndrome. This study- between certain nutrient intakes and physical activity with metabolic syndrome. Therefore, there is a need to address these problems at national and regional level with the aim of early identification and prevention and appropriate community based intervention program should be reinforced to increase the awareness of the community on healthy living.